Effect of in situ modification of bacterial cellulose with carboxymethylcellulose on its nano/microstructure and methotrexate release properties. (1st January 2018) - de Lima Fontes, Marina; Meneguin, Andréia Bagliotti; Tercjak, Agnieszka; Gutierrez, Junkal; Cury, Beatriz Stringhetti Ferreira; dos Santos, Aline Martins; Ribeiro, Sidney J.L.; Barud, Hernane S.
Highlights: Standard culture medium for BC production was in situ modified using CMC. It was observed coating islands on cellulose nanofibers after CMC addition. Degree of substitution of CMC plays a critical role on BC microstructure. Intermediate substitute CMC grade led to the slight lowering of MTX release rates. Abstract: Bacterial cellulose/carboxymethylcelullose (BC/CMC) biocomposites with different DS-CMC (DS from 0.7 to 1.2) were developed in order to evaluate their impact as a drug delivery system. Biocomposites were loaded with methotrexate (MTX) as an alternative for the topical treatment of psoriasis. Scanning electron microscopy and atomic force microscopy showed that the CMC coated the cellulose nanofibers, leading to the decrease of the elastic modulus as the DS of CMC increased. BC/CMC0.9 exhibited the lower liquid uptake (up to 11 times lower), suggesting that the more linear structure of the intermediate substitute CMC grade (0.9) was able to interact more strongly with BC, resulting in a denser structure. All samples showed a typical burst release effect in the first 15 min of test, however the BC/CMC0.9 biocomposite promoted a slight lowering of MTX release rates, suggesting that the DS of CMC can be considered the key factor to modulate the BC properties.